The Experiential Manasik Management Model in Worship Learning at Islamic Elementary Schools - Zahdi; Ahmad Zainuri; Khaf Shah (BASICA, 2025)
Islamic elementary education plays a strategic role in shaping students’ religious character and spiritual awareness from an early age. One increasingly relevant learning innovation in Madrasah Ibtidaiyah is the implementation of hajj and umrah ritual simulations (manasik) as a form of experiential learning that integrates cognitive, affective, and psychomotor aspects. Through these activities, students not only learn the procedural aspects of worship but also internalize values such as discipline, responsibility, cooperation, and sincerity. However, in many Islamic educational institutions, these activities have not been managed systematically in accordance with the principles of Islamic educational management, resulting in suboptimal effectiveness. This study aims to analyze the management of hajj and umrah ritual simulation activities in Madrasah Ibtidaiyah through three main management functions: planning, implementation, and evaluation. This research employs a qualitative method with a case study approach. Data were obtained from primary and secondary sources. Primary data involved 12 informants consisting of one madrasah principal, six supervising teachers, and five members of the manasik activity committee, while secondary data included planning documents, activity reports, and other supporting archives. Data were collected through participatory observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, with data validity strengthened through source and technique triangulation. The findings indicate that the implementation of manasik activities reflects spiritually value-based management, participatory involvement, and reflective evaluation of changes in students’ religious attitudes. This study produces the Experiential Manasik Management Model (MEMM), which integrates Islamic spiritual values with the modern management cycle, thereby contributing to the development of theory and practice in worship-based Islamic educational management.